Intermediate. Oxford Practice Grammar. With answers - Eastwood, John (Oxford University Press, 2019)
Refreshed with a new design, Oxford Practice Grammar is a three-level English grammar practice series for the classroom or self-study. Its tried and trusted methodology provides clear explanations and lots of extra practice. Includes downloadable progress tests with each level. Oxford Practice Grammar knows that students need different types of explanation and practice at each stage of their study. Basic provides lots of practice and short explanations; Intermediate gives you more detail with extended practice; Advanced gives challenging practice activities and in-depth explanations. Great for classroom or self-study.